Structural performance of confined masonry walls retrofitted using ferrocement and GFRP under in-plane cyclic loading. (1st July 2015) - El-Diasity, Mosaad; Okail, Hussein; Kamal, Osama; Said, Mohamed
Abstract: This paper presents the results of in-plane cyclic loading tests conducted on confined masonry walls retrofitted using low-cost ferrocement and GFRP systems. Ten wall assemblies with a 0.80-scale were built, consisting of a clay masonry panel, two confining columns and a tie beam. The assemblies were tested under a combination of a vertical load and lateral reversed cyclic loading with a displacement controlled loading protocol up to failure. Wall panels had various configurations, namely, solid walls, perforated walls with window and door openings. Two composite materials (ferrocement and GFRP) and three retrofitting configurations (diagonal "X", corner, and full coverage) were investigated. Key experimental results showed that the proposed upgrading techniques improved the lateral resistance of the confined walls by a factor ranging from 25% to 32%with a significant increase in the ductility and energy absorption of the panel ranging from 33% to 85%; however, the improvement in lateral drifts was less significant. Regarding the upgrading configurations, the diagonal "X" and full coverage can help prevent diagonal shear failure especially in tie columns and convert the failure mode to a panel-rocking mode. Additionally, in all retrofitting cases, collapse was significantly delayed by maintaining the wall integrity under large lateral deformations. A good agreement was found by comparing deformed shapes, crack patterns and capacity curves of finite element models included in this study.